Biomonitoramento genotóxico e genético como indicador de risco à saúde por exposição ao urânio de residentes dos municípios de Monte Alegre, Prainha e Alenquer no estado do Pará. - Sombra, Carla Maria Lima (2009)
Radiation is considered a risk factor for the development of several types of cancers caused by damage into the DNA molecule and is of extreme importance, therefore, the monitoring of human populations exposed to it. The municipality of Monte Alegre in the state of Pará in Brazil has one of the largest uranium mining areas of the world, which extends to the neighboring municipalities of Prainha and Alenquer. This work assessed the genotoxic potential of exposure to uranium in rocks found in dwellings in individuals from the municipalities of Monte Alegre, Prainha and Alenquer through the alkaline comet assay in peripheral blood lymphocytes and the determination of the frequencies of polymorphisms in DNA repair genes XRCC1 and XRCC3 and in carcinogen-metabolism gene GSTM1 through direct DNA sequencing. The analysis of the alkaline comet assay indicated that there was no statistically significant difference between the Damage Indexes (DIs) of Monte Alegre (DI = 32.01 ± 1.57), Prainha (DI = 45.80 ± 1.12) and Alenquer (DI = 44.30 ± 0.62) and of the negative control (DI = 42.00 ± 5.75) (p > 0.05). Through direct DNA sequencing, there were polymorphisms in XRCC1 and XRCC3 genes in regions of introns and exons. In XRCC1 gene, the variant allele frequencies for Arg194Trp polymorphism in Monte Alegre, Prainha and Alenquer populations were 12%, 13% and 7%, and for Arg399Gln, 28%, 30% and 32% respectively. In XRCC3 gene, the frequencies of the variant allele of Thr241Met polymorphism found in Monte Alegre, Prainha and Alenquer populations were, respectively, 28%, 13% and 33%. For GSTM1 gene, the frequencies obtained for the absence of this gene were 36%, 31% and 40%, respectively to Monte Alegre, Prainha and Alenquer populations. In general, the absence frequencies of GSTM1 gene and of allelic frequencies in XRCC1 and XRCC3 exons were statistically similar among the three municipalities and were in agreement with frequencies obtained in other studies with Brazilian populations. As a conclusion, among the populations studied, there was no increased incidence of DNA damage by exposure to uranium, which can be explained by the low radiation in these locations and that the allelic frequencies of polymorphisms found in the DNA repair genes XRCC1 and XRCC3, and the absence frequencies of GSTM1 gene did not differ from those in populations from other regions of Brazil. Thus, in the studied area, possibly there is no tendency to the development of cancer induced by exposure to uranium.